Management of Severe Epistaxis during Pregnancy: A Case Report and Review of the Literature - Maria Grazia Piccioni; Martina Derme; Laura Salerno; Elisa Morrocchi; Francesco Pecorini; Maria Grazia Porpora; Roberto Brunelli (Hindawi Limited, 2019)
Background. Epistaxis is a common problem during pregnancy. Few cases of severe epistaxis, not associated with nasal lesions or clotting disorders, were described in the literature. We reported a case of severe epistaxis in a pregnant patient, exploring all the different possible management options. Case. A 33-year-old primigravida, who was 38 weeks pregnant, presented with spontaneous severe left-sided epistaxis. Her blood pressure was into normal ranges. Clotting disorders and nasal lesions were excluded. The patient clinical worsening, due to severe anemia, and the failure of conservative treatment have imposed an emergency caesarean section, with an immediate resolution of the nasal bleeding. Conclusion. Treatment of severe epistaxis must always consider conservative measures first-line with early recourse to otolaryngologist. In general, delivery of the fetus is considered curative.